PENYELESAIAN TATA BATAS DAERAH OTONOM BARU (DOB) DI KALIMANTAN TENGAH - Slamet Winaryo (Journal Ilmu Sosial, Politik dan Pemerintahan, 2019)
Completion of boundaries in the New Autonomous Region in Central Kalimantan is aconceptual study of article to find out the extent of the implementation of the administrativeboundary delimitation in the New Autonomous Region in Central Kalimantan stipulated byLaw Number 5 of 2002 concerning the Establishment of 8 New Autonomous Regions inCentral Kalimantan. In this Law it is emphasized that the settlement of regional boundariesby no later than 2 years in New Autonomous Region 8 districts must be completed, asstipulated in the Decree of the Minister of Home Affairs No. 76 of 2012 concerningGuidelines for Confirmation of Regional Boundaries in an effort to create orderly government administration, provide clarity and legal certainty towards the boundaries of an area that meets technical and juridical aspects. The conceptual method of the article usingliterature study and or documentation studies relating to the implementation of regionalboundary. The results of a conceptual study of the implementation of regional boundarydelineation in the New Autonomous Region in Central Kalimantan, there are 23 boundarysegments, during the 17 years of implementation, which has been completed until 2019, asmany as 16 boundary segments (69.56%) while for 7 segments (30.44%) are not finished.The conclusion is the completion of regional boundaries cannot be completed in a short timeneeds. In order to complete 5 segments, it takes 13 years, while in 2017 the were 6 segmentscompleted, in 2018 there were 1 complete segment, and in 2019 there were only 4 segments.It takes a very long time of arguing and take a lot of time. Conclusion completion of theboundary requires a long time stages of preparation of documents, tracking, determiningcoordinates, making maps is not easy. The government does not have administrativeboundaries, but it must provide services to the community so that social problems arise.